Information giving and receiving in hematological malignancy consultations - Alexander, Stewart C.; Sullivan, Amy M.; Back, Anthony L.; Tulsky, James A.; Goldman, Roberta E.; Block, Susan D.; Stewart, Susan K.; Wilson-Genderson, Maureen; Lee, Stephanie J. (Psycho-oncology (Chichester, England), 2012)
Purpose: Little is known about communication with patients suffering from hematologic malignancies, many of whom are seen by subspecialists in consultation at tertiary‐care centers. These subspecialized consultations might provide the best examples of optimal physician–patient communication behaviors, given that these consultations tend to be lengthy, to occur between individuals who have not met before and may have no intention of an ongoing relationship, and which have a goal of providing treatment recommendations. The aim of this paper is to describe and quantify the content of the subspecialty consultation in regards to exchanging information and identify patient and provider characteristics associated with discussion elements. Methods: Audio‐recorded consultations between 236 patients and 40 hematologists were coded for recommended communication practices. Multilevel models for dichotomous outcomes were created to test associations between patient, physician and consultation characteristics and key discussion elements. Results: Discussions about the purpose of the visit and patient's knowledge about their disease were common. Other elements such as patient's preference for his/her role in decision‐making, preferences for information, or understanding of presented information were less common. Treatment recommendations were provided in 97% of the consultations and unambiguous presentations of prognosis occurred in 81% of the consultations. Unambiguous presentations of prognosis were associated with non‐White patient race, lower educational status, greater number of questions asked, and specific physician provider. Conclusion: Although some communication behaviors occur in most consultations, others are much less common and could help tailor the amount and type of information discussed. Approximately half of the patients are told unambiguous prognostic estimates for mortality or cure. Copyright © 2011 John Wiley & Sons, Ltd.